Factors related to patients’ readiness for advance care planning: a systematic review - Milad Asghardoust Rezaei; Ali Zahiri; Toktam Kianian; Elahe Hashemi; Ali Askari; Mobina Golmohammadi; Amir Mirsadeghi; Salman Barasteh (BMC Public Health)
Abstract Background Advance care planning can help to align the care provided with the values, goals and preferences of patients at the end of life. Therefore, readiness for advanced care planning is considered a prerequisite and predictor of the patient’s willingness to participate in the end of life conversation. The present study was conducted with the aim of investigating the factors affecting patients’ readiness for advance care planning (RACP). Methods This systematic review was searched in 4 databases: PubMed, Scopus, Web of science, ProQuest using relevant keywords. No time limit was considered. The quality of the articles was assessed using Joanna Briggs Institute tool for qualitative studies and the Appraisal Tool for cross-sectional Studies. The data was analyzed based on the directed content analysis approach guided by the theory of planned behavior (TPB). Results 3227 primary article titles were identified. After removing duplicates, screening and final selection, 22 relevant articles remained for analysis. Factors affecting RACP were extracted based on the TPB. Attitude factors include “ACP training”, “perceived experiences of health status”, “Socio-demographic factors”, and “psycho-spiritual readiness”. Subjective norms include “social support and family participation” and “accessibility to health services”. The perceived behavioral control includes “dialogue about ACP”, “readiness actions”, and “determining a proxy decision maker.” Conclusion In this study, according to the theory of planning behavior, various factors have an effect on the RACP. Therefore, according to the collaborative and multifactorial nature of the factors affecting preparation for ACP, it is suggested that different effective dimensions should be considered according to the specific conditions of each patient and the stage of the disease. Therefore, health service providers should first measure the level of readiness of patients and families, and by understanding the factors affecting their readiness, they should conduct training or dialogue in the field of ACP.